2020
DOI: 10.21037/atm.2020.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma irradiation on the measurement of hepatitis B virus DNA in dentin harvested from chronically infected patients

Abstract: Background: The manufacturing of the demineralized dentin matrix (DDM) has been proven to extensively reduce the presence of human hepatitis B viral DNA (HBV DNA). This study measured and compared HBV DNA in fresh dentin to that in gamma radiation (GR)-sterilized dentin extracted from HBVinfected patients. The application of GR as a means of terminal sterilization is hypothesized to inactivate or eliminate HBV within the dentin matrix.Methods: Dentin from 18 HBV-infected patients was collected and divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Since DDM does not have vascular channels nor a marrow space [ 51 ], the negative effect of irradiation could be diminished on DDM in comparison to DBM. In addition, the low antigenicity of DDM, due to the acellular nature of dentin, could reduce the irradiation dose required to reduce the risk of viral disease transmission [ 3 , 22 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since DDM does not have vascular channels nor a marrow space [ 51 ], the negative effect of irradiation could be diminished on DDM in comparison to DBM. In addition, the low antigenicity of DDM, due to the acellular nature of dentin, could reduce the irradiation dose required to reduce the risk of viral disease transmission [ 3 , 22 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although viruses show maximum resistance against irradiation, several studies have shown that the hepatitis C virus (HCV) and human immunodeficiency virus (HIV) are completely vulnerable to high doses of radiation [ 20 , 21 ]. In 2020, the effect of gamma irradiation with 15 and 25 kGy was a significant reduction of the HBV DNA levels in the fresh dentin matrix that was harvested from chronically infected patients [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sterilization using steam, dry heat and ethylene oxide all adversely influence teeth, while gamma sterilization reliably sterilizes teeth without causing changes to their composition or physical properties (Brauer et al, 2008; Rolland et al, 2007). It inactivates viral DNA within teeth and makes the samples safe to handle in the laboratory setting (Ku et al, 2020).…”
Section: Tooth Storagementioning
confidence: 99%
“…The double packing and sterilisation process were conducted using gamma irradiation. 26,28 The present research was approved by Health Research Ethical Clearance Commission, Universitas Airlangga, Faculty of Dental, Number 780/HERCC.FODM/X/2020, and was conducted at the Research Center, Faculty of Dental Medicine, Universitas Airlangga, Surabaya, Indonesia.…”
Section: Materials Examinedmentioning
confidence: 99%